Neutrality of coated holes in the presence of screw dislocation dipoles or circular thermal inclusions (Archives of Mechanics - Test, 2018)
In this paper, we consider the design of neutral coated holes in two particular cases when the thick coating itself is altered by the presence of some form of material imperfection. In the first case we consider anti-plane deformations of a linearly elastic solid when the thick coating applied to the hole includes a screw dislocation dipole. In the second case, we investigate the design of neutral coated holes in plane elasticity when the thick coating contains a circular thermal inclusion and the surrounding linearly elastic solid is subjected to uniform remote hydrostatic stresses. The design is achieved by constructing particular forms of the conformal mapping function for the coating itself. Several examples are presented to demonstrate the resulting solutions. Our numerical results show that the existence of the screw dislocation dipole or the circular thermal inclusion in the coating exerts a significant influence on the shape of the neutral coated hole.